PERILAKU SEKSUAL DITINJAU DARI PEMAHAMAN KONSEP REPRODUKSI MANUSIA, PERIIATIAN ORANG TUA DAN JENIS KELAMIN SISWA KELAS III SEMESTER GASAL SMA NEGERI 5 SURAKARTA TAHUN PELAJARAN - SANTOSA, SLAMET (Prodi Pendidikan Biologi FKIP UNS, 2006)
AbstractThe aims of this research are to know the influence of (1) human reproduction understanding (2)parental cares, (3) sexes and (4) interaction ofeach factor toward the sexual behavior ofthe students.The method used in this research was descriptive-quantitative method by expost facto. Research wascarried out upon 3 rd grade students of SMA N 5 Surakarta as the population that sampled. The samplingtechnique used was random sampling technique which sampled l2O students. The data collected by usingevaluation (test) method, documentation and anquette and analyzed by using analyses of variance.Statistical results showed that (1) the influence of human reproduction understanding toward sexualbehavior is (Fo > Ft= 5.23 > 5.18), (2) parental cares toward sexual behavior is ( Fo > Ft = 12.654 > 5.18), (3)sexes toward sexual behavior is ( Fo > Ft = 70.712 > 5.18), (4) interaction between human reproductionunderstanding and parental cares toward sexual behavior is ( Fo > Ft = 5.666 > 5.18), (5) interaction betweenhuman reproduction understanding and sexes toward sexual behavioris ( Fo > Ft = 7 .701 > 5.18), (6) interactionbetween parental cares and sexes toward sexual behavior is ( Fo > Ft = 10.295 > 5.18), (7) interaction among thethree factors toward sexual behavior is ( Fo> Ft = 5.364 > 5.18).Key Words: Sexual behavior, human reproduction understanding, parental cares, sexes